2009
DOI: 10.1111/j.1530-9290.2009.00171.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Precious Metal Flows During Preprocessing of Waste Electrical and Electronic Equipment

Abstract: Keywords:industrial ecology printed circuit board (PCB) recycling resource recovery substance flow analysis (SFA) waste electrical and electronic equipment (WEEE) SummaryThe manufacturing of electronic and electrical equipment (EEE) is a major demand sector for precious and special metals with a strong growth potential. Both precious and special metals are contained in complex components with only small concentrations per unit. After the use-phase, waste electronic and electrical equipment (WEEE) is an import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
153
1
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 312 publications
(167 citation statements)
references
References 31 publications
2
153
1
6
Order By: Relevance
“…Despite the huge efforts to perform this practice in a controlled way, many illegal domestic and backyard recycling is still occurring, generally in overseas countries (Yoshida 2011;Duan et al 2016). This results in a growing uncontrolled trade with WEEE-related polymeric waste streams, aluminium, ferrous and nonferrous metals (Chancerel et al 2009;Guo et al 2009;Dwivedy & Mittal 2010;Kahhat & Williams 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Despite the huge efforts to perform this practice in a controlled way, many illegal domestic and backyard recycling is still occurring, generally in overseas countries (Yoshida 2011;Duan et al 2016). This results in a growing uncontrolled trade with WEEE-related polymeric waste streams, aluminium, ferrous and nonferrous metals (Chancerel et al 2009;Guo et al 2009;Dwivedy & Mittal 2010;Kahhat & Williams 2012).…”
Section: Resultsmentioning
confidence: 99%
“…For example, Chancerel et al ( 2009 ) assessed precious metal fl ows during preprocessing of waste electrical and electronic equipment and showed that only 11.5 % of the silver and 25.6 % of the gold and of the palladium reach output fractions from which they can potentially be recovered.…”
Section: Spatial System Boundariesmentioning
confidence: 99%
“…Electronic waste (e-waste) has been recognised as one of the fastest growing waste streams in the developed world, mainly due to advances in the electronics industry that render technology obsolete after only a few years [1,2]. This can lead to potential environmental problems as a proportion of the waste contains toxic metals such as Hg (II), Pb(II) or Cr(VI).…”
Section: Introductionmentioning
confidence: 99%